The untapped potential of Games for Health in times of crises. A critical reflection - Dadaczynski, Kevin; Tolks, Daniel; Wrona, Kamil J.; Mc Call, Timothy; Fischer, Florian (Frontiers in Public Health, 2023)
Given its promising role in public health to address hard to reach population groups, game-based interventions (i.e., Games for Health, G4H) have experienced growing interest in recent years. Therefore, it is surprising that they have played only a minor role during the COVID-19 pandemic. Hence, the aim of this paper is to reflect the opportunities and challenges of G4H especially during the pandemic but also with regard to future health crises. As commercial video games (i.e., those that primarily aim to entertain its users) were often used to deal with the containment measures during the COVID-19 pandemic, we call for greater cooperation with commercial game makers to distribute health-relates messages via entertainment games. With regard to G4H we see a need to (i) strengthen the intervention theory underlying game-based applications, (ii) to enhance game appealing in order to maintain the interest of users in the long term, and (iii) to improve the evidence base using appropriate study designs. Finally, we argue for greater user involvement, both in terms of developing game-based approaches and as co-researchers in solving complex health problems.